2020
DOI: 10.1038/s41598-020-67766-0
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture at Zusanli and at Neiguan characterized point specificity in the brain by metabolomic analysis

Abstract: Different point stimulations can induce brain activity in specific regions, and however whether these stimulations affect unique neurotransmitter transmission remains unknown. Therefore, we aimed to investigate the effect of point specificity to the brain by resolving the metabolite profiles. Eighteen Sprague-Dawley rats were randomly divided into three groups: (1) the sham group: sham acupuncture at Zusanli (ST36) without electric stimulation; (2) the Zusanli (ST36) group: electroacupuncture (EA) at ST36; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 31 publications
(31 reference statements)
2
20
0
2
Order By: Relevance
“…Three acupoints are shown in the middle human picture in Figure 6, namely, Zhongwan acupoint in the abdomen, [ 42 ] Hand Sanli acupoint in the left arm, [ 43 ] and Zusanli acupoint in the right leg. [ 44 ] Figure 6b shows the example of an electric heating device used on Hand Sanli acupoint. The bright spot of the heating device means a good heating effect.…”
Section: Resultsmentioning
confidence: 99%
“…Three acupoints are shown in the middle human picture in Figure 6, namely, Zhongwan acupoint in the abdomen, [ 42 ] Hand Sanli acupoint in the left arm, [ 43 ] and Zusanli acupoint in the right leg. [ 44 ] Figure 6b shows the example of an electric heating device used on Hand Sanli acupoint. The bright spot of the heating device means a good heating effect.…”
Section: Resultsmentioning
confidence: 99%
“…This was performed once a day for 20 minutes each, from the 7th day after modeling for a total of 21 days, as previously described. 22 , 23…”
Section: Methodsmentioning
confidence: 99%
“…ST36 can be used to treat cardiovascular disorders such as precordial pain and palpitation, whereas PC6 can be used to treat digestive disorders such as vomiting and stomachache 11 , 12 . Our previous metabolomic analysis revealed that EA at PC6 and ST36 induces multiple neurotransmitter profiles in the cerebral cortex and hippocampus of rats 1 . Therefore, in this study, we performed metabolite profiling to determine the effects of EA at PC6 and ST36 on the metabolism of rat heart and stomach tissues.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, acupuncture signals are transmitted via the Neiguan acupoint (PC6) to the heart. This concept is called “acupoint specificity.” Our previous study demonstrated that 2-Hz electroacupuncture (EA) applied to ST36 and PC6 can affect neurotransmitter levels in multiple areas of the brain 1 . Both the stomach and heart are closely related to energy generation and metabolism, and acupuncture at ST36 can induce multiple metabolic pathways in serum, including glycerophospholipid and fatty acid metabolism 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%